Concurrent experiences of work engagement and workaholism: A factor-level profile analysis. (February 2023) - Cook, Ryan; Gilin, Debra
Abstract: Work engagement and workaholism are two forms of being heavily invested in work, with the former usually framed positively and the latter framed negatively. Although there is a wealth of literature for each construct separately, less is known about how these two constructs may be experienced concurrently. The current study builds on previous research by conducting a latent profile analysis (LPA) of engagement and workaholism at the factor-level. It was determined that there were five profiles in the data, described as Uninvested (low on workaholism factors and low on engagement factors; 6.73 %), Just Content (average-average; 27.61 %), Workaholics (high-average; 35.02 %), Engaged (average-high; 19.19 %), and Engaged Workaholics (high-high; 11.45 %). Interestingly, the Uninvested profile reported the highest burnout and turnover intent compared to all other profiles, with Workaholics also scoring worse than the Engaged and Engaged Workaholic profiles, which did not differ compared to each other. The Engaged profile reported significantly less work-to-family conflict than the Engaged Workaholic, Workaholic, and Just Content profiles, which did not differ. Theoretical and practical implications are discussed.